Penerapan Konsep Berbasis Customer Relationship Management (CRM) terhadap Pelayanan Tamu pada Hotel Grand Royal Denai Kota Bukittinggi - Lutfi Nurul Khairiyah Dinata; Awaluddin Awaluddin (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
The background of this study is based on the importance of implementing CRM strategies in the hospitality industry, particularly in facing business competition challenges and meeting the ever-evolving needs and expectations of customers. In the context of sharia tourism, which is beginning to develop in West Sumatra, good service and long-term relationships with guests are significant added values for the sustainability of a hotel. The objective of this study was to determine how the CRM concept is implemented at Hotel Royal Denai Bukittinggi, and to what extent CRM contributes to building customer loyalty. This study uses a qualitative approach with a descriptive method. Data was collected through in-depth interviews with the Human Resource Development (HRD) department, direct observation of guest service activities, and relevant documentation studies.The research findings indicate that the implementation of CRM at Hotel Royal Denai is still not optimal. The hotel does not yet have an integrated customer data management system, and its communication strategies with guests remain conventional and lack sustainability. Additionally, certain aspects of service, such as the completeness of room facilities, the speed of response to guest complaints, and the friendly attitude of staff, still need improvement. However, the management acknowledges the importance of CRM as a key strategy for enhancing customer satisfaction and fostering long-term relationships with guests.